2020
DOI: 10.1007/s00167-020-06018-0
|View full text |Cite
|
Sign up to set email alerts
|

Anterior root of lateral meniscus and medial tibial spine are reliable intraoperative landmarks for the tibial footprint of anterior cruciate ligament

Abstract: PurposeThe aims of the present study were (1) to investigate the tibial footprint location of the anterior cruciate ligament (ACL) in both ACL‐ruptured and ACL‐intact patients, (2) to identify the relationship of the tibial footprint to the anterior root of the lateral meniscus (ARLM) and medial tibial spine (MTS), and (3) to evaluate the reliability of the ARLM and MTS for identifying the center of the tibial ACL footprint. MethodsMagnetic resonance images of 90 knees with ACL rupture and 90 matched‐controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…The tibial spine can be regarded as a bony landmark for tibial tunnel positioning. 2 A previous study investigated the correlation between the location of the tibial spine and the ACL footprint morphology with the TSP technique, and the results indicated that the location of the tibial spine was likely to influence tibial tunnel placement. 5 Both techniques positioned the tibial tunnel medially in comparison to the anatomic site.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The tibial spine can be regarded as a bony landmark for tibial tunnel positioning. 2 A previous study investigated the correlation between the location of the tibial spine and the ACL footprint morphology with the TSP technique, and the results indicated that the location of the tibial spine was likely to influence tibial tunnel placement. 5 Both techniques positioned the tibial tunnel medially in comparison to the anatomic site.…”
Section: Discussionmentioning
confidence: 99%
“…By comparatively analyzing the magnetic resonance imaging scans of an ACL-ruptured group and an ACL-intact group, Dimitriou et al 2 found that the medial tibial ridge and ARLM might be used as reliable landmarks for anatomic ACL reconstruction. In the present study, it was found that the location of the MLTS did not differ between the 2 groups, suggesting that the MLTS is a reliable anatomic landmark for tibial tunnel placement, with little variation between patients (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, the structural relationship between the ACL and articular cartilage has not yet been reported. Conventionally, it was believed that the tibial side of ACL did not attach to the articular cartilage, and only its attachment to the bone surface was analyzed 7 , 10 14 , 16 , 20 , 22 41 . In contrast, several studies have reported the close relationship of the tibial side of ACL with LM, describing it as an “overlap,” “adjoin,” or “adjacent” 7 , 11 , 12 , 14 17 .…”
Section: Discussionmentioning
confidence: 99%